Determinant of The Corporate Environmental Disclosure: Study on Jakarta Islamic Index - Yulianti, Yulianti; Suzanawaty, Leis; Putri, Zuwesty Eka; Haribowo, Ismawati (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2016)
The issue about corporate environment disclosure nowadays is increasing. This research aims to analyze the influence of firm size, leverage, proportion of independent commissioners, corporate secretary and firm age to corporate environmental disclosure. Thirteen companies that listed at Jakarta Islamic Index during 2011-2014 are used as sample. Data was analyzed using multiple regression technique. The independent variables are firm size, leverage, and proportions of independent commissioners, corporate secretary, and firma age. The result shows that simultaneously all independent variables have significant influence to corporate environmental disclosure. Whereas partially, firm size and firm age have significantly influence to corporate environmental disclosure. The implication of this research is the larger of the firm size and the longer firm will make a better corporate environmental disclosure in companies that listed at Jakarta Islamic Index.DOI: 10.15408/aiq.v8i2.3158